Epilepsy surgery in the first 3 years of life: predictors of seizure freedom and cognitive development - Kadish, Navah; Bast, Thomas; Reuner, Gitta; Wagner, Kathrin; Mayer, Hans; Schubert-Bast, Susanne; Wiegand, Gert; Strobl, Karl; Brandt, Armin; Korinthenberg, Rudolf; van Velthoven, Vera; Schulze-Bonhage, Andreas; et al. (Neurosurgery, 2019)
AbstractBACKGROUND. Although the majority of children undergoing epilepsy surgery are younger than 3 yr at epilepsy manifestation, only few actually receive su